THE CORRELATION BETWEEN STUDENTS’ HABIT IN WATCHING MOVIE AND LISTENING SKILL - Usman Abdullah; Indah Fadhilah Rahman (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
This study aimed to find and describe the relationship between students’ habit in watching English movie (variable x) and their listening skill (variable y). This study was conducted at the English Education Department of Tarbiyah and Teaching Science Faculty of UIN Alauddin Makassar. The population in this study was all of the first-semester students in the academic year 2016/2017 which consisted 102 students, and the sample taken was 30 students by using random sampling. The method used in this study was the quantitative method with the correlational design. The instruments used to gather the data were questionnaire and test. The scores from both instruments were calculated and analyzed by using statistical procedure of Product Moment Correlation to see whether there was a correlation between the two variables or not. The result showed that there was a correlation, with the index value of correlation coefficient (rxy) of 0.444 which meant there was a moderate correlation. Furthermore, the hypothesis testing showed that the index value of correlation coefficient (rxy) of 0,444 was higher than the index value of correlation coefficient of the Product Moment table (rt) of 0,306 which meant that the null hypothesis (H0) was rejected and alternative hypothesis (H1) was accepted. In conclusion, there was a moderate significance correlation between the two variables. Based on the findings mentioned above, the researcher assumes that the more students watching English movie the more their listening skill will be better which means movie can be used as media to improve students’ listening skill. Therefore, the researcher suggests that the English teacher could use movie as a media in language teaching in improving students’ listening skill.